Prediction Qualities of the Ifo Indicators on a Temporal Disaggregated German GDP - Christian Seiler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
This paper compares the German Gross Domestic Product between 1991 and 2008 with the Ifo business indicators. Because GDP is published quarterly but the Ifo indicators monthly, the most analyses compare these variables by merging the indicators to quarterly data. In this paper an alternative way is shown: GDP will be disaggregated with ECOTRIM, a software package from Eurostat, to get monthly data. Furthermore, a spline-based disaggregation approach is discussed. The results of the analyses demonstrate a high connection between the disaggregated GDP and the Ifo indicators.
Keywords: 330; Temporal disaggregation; indicators; Gross Domestic Product; splines